THE SOCIAL REALITY OF EGYPTIAN SOCIETY IN 1967 AD IN THE NOVEL AL KARNAK BY NAJIB MAHFUDZ - Heniatus Zahroh; Abdul Basid (Faculty of Humanities UIN Maulana Malik Ibrahim Malang, 2022)
Social reality is a picture of phenomena that occur in society. Both in the real world and some literary works, such as in the novel Al-Karnak by Najib Mahfudz. This type of research is qualitative descriptive research, data collection techniques are reading, and note-taking strategies. Data analysis used data reduction techniques, data presentation, and conclusion. The aims of this study are: (1) To reveal the social reality of the material type depicted in Najib Mahfudz's novel Al-Karnak based on Emile Durkheim’s perspective ; (2) Revealing the social reality of the non-material type depicted in the novel Al-Karnak by Najib Mahfudz using Emile Durkheim's perspective. The results of this study are: (1) the social reality of the type of material in the novel Al-Karnak by Najib Mahfudz using Emile Durkheim’s perspective is buildings, electronics, and regulations; (2) Non-material social reality in Najib Mahfudz's novel Al-Karnak usingEmile Durkheim's perspective is morality, collective consciousness, collective representation, social currents, and collective mind.